Exploring the Herbicidal Potential of Achyranthes aspera Against Some Weeds - TANVEER,A. (2019)
ABSTRACT: The phytotoxic composition of Achyranthes aspera was identified through HPLC, and its herbicidal potential was investigated against two narrow leaf weeds viz., Phalaris minor Retz. and Avena fatua L.; and four broad leaf weeds viz. Lathyrus aphaca L., Vicia sativa L., Convolvolus arvensis L. and Asphodelus tenuifolius L. through bioassays. Weed seeds were grown in the aqueous extracts of various plant parts (roots, leaf, stem, fruit and whole plant) of A. aspera at 5% (w/v) concentration. The extracts of all plant parts caused significant reductions with differential degree in germination percentage and mean germination time. Phalaris minor, A. fatua, L. aphaca, V. sativa and A. tenuifolius completely failed to germinate whereas C. arvensis showed the lowest GP (20%) in response to 5% fruit extract of A. aspera. Inhibition of seed germination of all weeds was higher with the fruit extract than with the root, stem, leaf and whole plant extracts of A. aspera. Seed germination of all narrow leaf weeds was completely inhibited at the 5% fruit extract of A. aspera. The highest phytotoxic inhibitory effect of A. aspera fruit extract was proved to be due to the presence of gallic acid (88.4 mg kg-1), caffeic acid (519.2 mg g-1) and m-coumaric acid (51.4 mg kg-1) as assessed by their HPLC analyses. The study, therefore, showed that A. aspera exerts an inhibitory effect on germination of weeds and can be further explored as a pre- or post-emergence herbicide to provide natural alternative to chemical herbicides in the future.